Millennium: Food for thought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Your comments on the Millennium supplement, Scenarios for ACP agriculture: Joining the circles of life, have started to arrive at the Spore offices. Among the first, lengthy reflections was one from Ms Thiam Traoré Djenebou, Director of SUD AGORA,...